Ultra-high phase-locked harmonic generation from magnetic transversal confinement of electrons - Plaja Luis; Martín-Hernández Rodrigo; Hu Hongtao; Baltuska Andrius; Hernández-García Carlos (EPJ Web of Conferences, 2023)
The technological refinements on high-power laser systems of Petawatt class unveil scenarios for light-matter interaction beyond the laser-plasma perspective. In this contribution we explore the possibility of assisting high-harmonic generation (HHG) with the strong magnetic field associated with one of those intense sources. Recently, there has been an interest in developing schemes to employ intense laser beams to define spatial volumes in which strong magnetic fields are found isolated from the electric field. In this conditions, the magnetic field can be used to assist the harmonic generation from atoms from standard drivers. We demonstrate that, using the proper interaction geometry, the magnetic field confines the transversal dynamics of the con-tinuum electrons allowing, on one side, to enhance the efficiency of the electron rescattering that produces the harmonic radiation and, on the other side, to excite the electron transverse dynamics and to convert this energy into phase-locked harmonic photons of few hundreds of eV.